AREAS OF IMPROVEMENT OF LEGAL REGULATION OF PERSONNEL SERVICE PROVISION - Andryeyev, A. (Київський національний університет імені Тараса Шевченка, 2019)
It is stated that the current legal regulation of the personnel support of the civil service of Ukraine does not fully satisfy the needs of the society for the purposes of ensuring the fulfillment of the tasks set, and therefore the issues related to the improvement of the existing mechanisms are still not relevant, since the proper functioning of the state institutions is impossible without a skilled and powerful state apparatus. The list of problems of legal regulation of the civil service personnel is determined. Suggestions are made to address these issues. It is established that one of the problems of legal regulation of the personnel support of the civil service of Ukraine under the national legislation is the imperfection of the current legislation in this field, which creates "hidden opportunities for positions". Attention was drawn to the need to address corruption issues, in particular, the strengthening of control by staffing services was proposed. For example, when recruiting a candidate for a civil servant position, the HR should, along with checking education data, work experience, etc., pay attention to identifying moral and ethical qualities and the absence of allegations of corruption in the past. The article analyzes the aspects of optimization of legal regulation of public service personnel. It is proposed to optimize the legal regulation of the staffing of the civil service of Ukraine in several stages in order to increase the level of professional competence of civil servants. Some researchers have expressed their views on this issue, of which the proposal to focus attention on attracting young creative personnel to the civil service is particularly interesting. In this case, it is advisable to amend Article 19 of the Law of Ukraine "On Civil Service" of 10.12.2015 No. 889-VIII with the establishment of the maximum age of admission to the position of civil service, which in practice can really contribute to the formation of a qualitatively new composition of civil servants. You can set an approximate age of 30 years. Among the areas of optimization of the legal regulation of the personnel support of the civil service of Ukraine, at the stage of raising the level of professional competence of civil servants, the extension of the personal responsibility of civil servants is highlighted. The main problems for today are that the current Law of Ukraine “On Civil Service” of December 10, 2015 No. 889-VIII provides only two types of liability of civil servants - disciplinary and material. In the Criminal Code of Ukraine and the Code of Ukraine on Administrative Offenses, firstly, the legislator does not use the term "civil servant", and secondly, there are no sections directly related to the offenses and crimes of public servants in the structure of these normative legal acts. the rules may be contained in different sections of the codes.

Зазначено, що чинне правове регулювання кадрового забезпечення державної служби України на сьогодні не в повній мірі задовольняє потреби суспільства у питаннях забезпечення виконання поставлених завдань, а тому все ще не втрачають актуальності питання, пов’язані із вдосконаленням існуючих механізмів, адже належне функціонування державних інститутів неможливе без кваліфікованого і потужного державного апарату. Визначено перелік проблем правового регулювання кадрового забезпечення державної служби. Сформульовано пропозиції щодо вирішення вказаних проблем. Встановлено, що однією із проблем правового регулювання кадрового забезпечення державної служби України за національним законодавством є недосконалість чинного законодавства у даній сфері, що створює «приховані можливості посад». Звернено увагу на необхідність вирішення проблем корупції, зокрема запропоновано посилення контролю із боку кадрових служб. Так, приймаючи кандидата на посаду державного службовця, кадрова служба повинна поряд із перевіркою даних про освіту, досвіду роботи тощо приділяти увагу з’ясуванню морально-етичних якостей та відсутності звинувачень у корупційних діях у минулому. У статті проаналізовано аспекти оптимізації правового регулювання кадрового забезпечення державної служби. Запропоновано здійснити за декількома етапами оптимізацію правового регулювання кадрового забезпечення державної служби України для підвищення рівня професійної компетентності державних службовців. Висловлені точки зору окремих дослідників стосовно цього питання, особливо цікавою з яких є  пропозиція акцентування уваги на залученні до державної служби молодих креативних кадрів. У такому разі доцільним є внесення змін до статті 19 Закону України «Про державну службу» від 10.12.2015 № 889-VIII із встановленням граничного віку прийняття на посаду державної служби, що  на практиці може дійсно посприяти формуванню якісно нового складу державних службовців. Орієнтовний граничний вік можна встановити у розмірі 30 років. Серед напрямків оптимізації правового регулювання кадрового забезпечення державної служби України на етапі підвищення рівня професійної компетентності державних службовців в першу чергу виділено розширення персональної відповідальності державних службовців. Основними проблемами на сьогодні є те, що в чинному Законі України «Про державну службу» від 10.12.2015 № 889-VIII передбачено лише два види відповідальності державних службовців – дисциплінарна та матеріальна. У Кримінальному кодексі України та Кодексі України про адміністративні правопорушення, по-перше, законодавець не оперує терміном «державний службовець», а, по-друге, в структурі даних нормативно-правових актів відсутні розділи, присвячені безпосередньо правопорушенням та злочинам державних службовців, а відповідні норми можуть міститись у різних розділах кодексів.
НАПРЯМИ УДОСКОНАЛЕННЯ ПРАВОВОГО РЕГУЛЮВАННЯ КАДРОВОГО ЗАБЕЗПЕЧЕННЯ ДЕРЖАВНОЇ СЛУЖБИ
Keywords: improvement; legal regulation; human resources; civil service; civil servant.; удосконалення; правове регулювання; кадрове забезпечення; державна служба; державний службовець.